Organizacija in svoboda - analiza skladbe Tongenesis Uroša Rojka - Vrhunc, Larisa (Muzikološki zbornik, 2010)
Among the pieces by Uroš Rojko Tongenesis is probably the most consistently organized. The aim of the analysis is to show by what means the author "fought his way out" to sufficient freedom in working with systems, so that in the final realization of the score his music prevailed over the logic of system-generated music matter.
Keywords: 20.st.; 20th century; analiza glasbe; music analysis; music theory; Rojko, Uroš, 1954-; Rojko, Uroš: Tongenesis; Slovenian music; slovenska glasbe; teorija glasbe